2019
DOI: 10.3389/fphys.2019.01421
|View full text |Cite
|
Sign up to set email alerts
|

Liver Cirrhosis Patients Who Had Normal Liver Function Before Liver Cirrhosis Development Have the Altered Metabolic Profiles Before the Disease Occurrence Compared to Healthy Controls

Abstract: Liver cirrhosis (LC) is the final usual outcome of liver damage induced by various chronic liver diseases. Because of asymptomatic nature of LC, it is usually diagnosed at late and advanced stages, and patients are easy to miss the best timing for treatment. Thus, the early detection of LC is needed. In the prospective Korean Cancer Prevention Study-II (K-II), we aimed to identify valuable biomarkers for LC using metabolomics to distinguish subjects with incident LC (LC group) from subjects free from LC (contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 49 publications
1
30
0
Order By: Relevance
“…Considering mounting evidence supported that long-term complications can be prevented by optimizing metabolic control, we recommend an aggressive therapy for GSD VI [30]. Systematic follow-up and specific biomarkers are also needed to monitor this silent course although the improvement of elevated transaminase was observed in most of our patients with GSD VI [15,33]. Kobayashi et al concluded that variants with an allele frequency higher than 0.01% in the ExAC database were generally already well characterized in the literature as known founder mutations [34].…”
Section: Discussionmentioning
confidence: 98%
“…Considering mounting evidence supported that long-term complications can be prevented by optimizing metabolic control, we recommend an aggressive therapy for GSD VI [30]. Systematic follow-up and specific biomarkers are also needed to monitor this silent course although the improvement of elevated transaminase was observed in most of our patients with GSD VI [15,33]. Kobayashi et al concluded that variants with an allele frequency higher than 0.01% in the ExAC database were generally already well characterized in the literature as known founder mutations [34].…”
Section: Discussionmentioning
confidence: 98%
“…Bile acids are an example of a potential common serum biomarker of liver diseases. A potential prognostic biomarker was identified by a metabolomics prospective study where serum fatty acids, including linoleic and α-linoleic acids, were lower before the occurrence of cirrhosis in patients in comparison to healthy controls [ 25 ]. The observed model-specific changes in transcriptome signatures could reflect the unique metabolic rearrangements among fibrotic models ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Activated HSCs are known to enhance the expression of TGF-β, COL1A1, α-SMA, TIMP, and PAI-1, which are involved in liver brosis [33][34][35][36][37][38] . Previous studies have shown that blood PA concentrations in cirrhotic patients are associated with the degree of liver brosis and that PA concentrations were high even before the onset of cirrhosis 39,40 . We showed that intestinal PA absorption and PA concentration in portal blood were increased in NASH rats.…”
Section: Discussionmentioning
confidence: 99%